2019
DOI: 10.1080/13102818.2018.1555011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional analysis of a sugar transporter gene (CsTST2) from cucumber (Cucumis sativus L.)

Abstract: View related articles View Crossmark data Citing articles: 4 View citing articles Molecular cloning and functional analysis of a sugar transporter gene (CsTST2) from cucumber (Cucumis sativus L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Source-to-sink transport of sugars can modify the carbohydrate distribution and homeostasis that contribute to the tolerance of plants to abiotic stresses [54,72]. Many SWEET genes were regulated by various abiotic stresses, suggesting that they may play regulatory roles in the responses to various abiotic stresses by controlling sugar allocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Source-to-sink transport of sugars can modify the carbohydrate distribution and homeostasis that contribute to the tolerance of plants to abiotic stresses [54,72]. Many SWEET genes were regulated by various abiotic stresses, suggesting that they may play regulatory roles in the responses to various abiotic stresses by controlling sugar allocation.…”
Section: Discussionmentioning
confidence: 99%
“…The qRT-PCR reactions were performed in 20 μL reactions using 1 μL of cDNA, with the FastStar Universal SYBR Green Master (ROX) (Roche Diagnostics, Indianapolis, IN, USA), on the ABI 7500 system (Thermo Fisher Scientific, Waltham, MA, USA). The qRT-PCR conditions were as described previously [54]. Three independent biological replicates were conducted.…”
Section: Methodsmentioning
confidence: 99%
“…The authors observed that salt stress modulated the expression of SUCROSE SYNTHASE ( SUSY1 ), and different sugar transporters such as TMT and SWEET and, also induced alterations in the vascular anatomy of the inflorescence stem (Sellami et al, 2019). Hu et al (2019) identified 25 SWEET genes in the Medicago truncatula genome and reported that half of the MtSWEET genes demonstrated significant transcript accumulation in cold, salt and drought stresses. Besides this, the transcript levels of seven genes including MtSWEET1a , 2b , 3c , 9b , 13 , 15c , and 16 are significantly altered by drought, salt, and cold treatments (Hu et al, 2019).…”
Section: The Interplay Between Sugars and Phytohormones Under Abiotic Stressmentioning
confidence: 99%
“…Unlike all other plants, in the Solanaceae family, type III SUTs (SUT4 here) have been localized to the plasma membrane instead of the tonoplast (Chincinska et al, 2008). A tonoplast sugar transporter (TST), CsTST2 from Cucumis sativus (cucumber), was also found to be upregulated during various abiotic stresses like salt, drought, and cold and was proposed to import fructose, galactose, mannose, and sucrose inside the vacuoles (Hu et al, 2019). Even though potato SUT4 has been characterized to be a highly efficient sucrose transporter, its decreased expression during drought stress indicated that it is unlikely to be directly involved in phloem loading.…”
Section: Sugar Status Impacts Source‐sink Relationship During Droughtmentioning
confidence: 99%